THE EFFECTIVENESS OF THE SINERGISMART-INFO HARGA APPLICATION IN CONTROLLING PRICE FLUCTUATIONS OF ESSENTIAL GOODS - Zidana, Abdullah; Balahmar , Ahmad Riyadh Umar (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of the SinergiSmart–Info Harga Application in controlling price fluctuations of essential goods in Mojokerto Regency. The research focuses on four indicators of program effectiveness as proposed by Budiani, namely target accuracy, socialization, objectives, and program monitoring. Method: The method used is a descriptive qualitative approach, with data collected through observation, interviews, and documentation at the Department of Industry and Trade of Mojokerto Regency. Data analysis employed the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. Results: The research results indicate that the SinergiSmart–Info Harga application is quite effective in terms of target accuracy and program monitoring indicators. The application successfully reaches a wide range of users, including consumers, MSME actors, and policymakers, and serves as an early detection tool for price fluctuations that facilitates government interventions, such as market operations. However, its effectiveness in the areas of program dissemination and goal achievement remains suboptimal. The lack of formal dissemination efforts has resulted in a relatively low number of users, while limitations in features such as price trend graphs and commodity stock availability information restrict the application’s ability to comprehensively support price fluctuation control. Novelty: The novelty of this research lies in its focus on analyzing the effectiveness of the SinergiSmart–Info Harga digital-based application at the regional level, involving direct perspectives from both government institutions and user communities. This study highlights the application's potential as a digital ecosystem that not only provides real-time price information but also serves as a strategic instrument for local governments in maintaining price stability and public purchasing power.